Clinical Features and Long-Term Outcomes of Systemic Lupus Erythematosus - Sjöwall, Christopher; Parodis, Ioannis (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The clinical spectrum of systemic lupus erythematosus (SLE) is highly heterogeneous, ranging from mild disease, which can be limited to skin and joint involvement, to life-threatening conditions with renal impairment, severe cytopenias, central nervous system disease, and thromboembolic events. Apart from the host genetics, several environmental factors, such as sunlight, infections, drugs, and probably hormonal factors, can trigger the onset of symptoms related to SLE. Despite significant advances in our understanding of the pathophysiology and optimization of medical care, patients with SLE still have significant rates of premature mortality and many patients experience severe disease with increased risk of sustaining organ damage and having a reduced health-related quality of life. The development of effective drugs that can induce remission or low disease activity, the unanimous use of definitions of remission and low or high disease activity, flare, and response to therapy, the identification of non-invasive biomarkers of disease activity and long-term outcomes, and the implementation of SLE patients' perspectives as an integral part of the clinical assessment constitute only a few of the many unmet needs in the field of SLE.